Implementation of Discovery Learning in Human Digestive System Learning for Grade VIII Students - Much Fuad Saifuddin; Jihad Wintolo; Dian Oktaviani; Agustina Novitha Anggraini; Hilda Zulfi Maulidya; Yuli Suprihatin; Ayu Fitria; Febriyeni Febriyeni; Destri Ratna Ma'rifah (Bioeducation Journal, 2020)
Student learning outcomes in learning in class VIII SMP Muhammadiyah 9 Yogyakarta is still low. Factors causing low learning outcomes include not using any learning model and still being teacher-centered. This study aimed to determine the effect of Discovery learning learning models on student learning outcomes in the digestive system material class VIII at SMP Muhammadiyah 9 Yogyakarta. This type of research is a quasi-experiment. This study's population were all VIII grade students of SMP Muhammadiyah 9 Yogyakarta consisting of five classes, namely classes A, B, C, D, and E, with 140 students. In this study, purposive sampling was conducted based on certain considerations so that 2 class samples were obtained, namely class VIII C as the control class and VIII E as the experimental class. Data collection techniques with tests. Data collection instruments were in the form of pretest and posttest questions. The analysis technique used is descriptive quantitative. Research Results Learning outcomes were analyzed by t-test statistics at the level of significance 5% obtained t-count 0.302 and t-table = 2.01063, so t-count < t-table. Therefore, the Discovery learning model does not affect the learning outcomes of VIII grade students of SMP Muhammadiyah 9 Yogyakarta.